Implementasi Permainan Papan "Jelajah Budaya Panrita Lopi" Dalam Meningkatkan Kemampuan Membaca Pemahaman Siswa Kelas V SDN 131 Bontobana - Nurul Amadyah; Aco karumpa; Desy Ayu Andhira (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
This research used an experimental design, and the data were processed using SPSS version 25 for Windows, with a sample of 20 Grade V students. Data collection for this research used Pretest, Treatment/Action in the form of implementing the board game "Cultural Exploration of Panrita Lopi". After the action was completed, a Posttest was conducted to measure the students' reading comprehension skills once again. This data was used to compare the results before and after the intervention.The results of the research clearly show that there was a significant improvement in the reading comprehension skills of Grade V students at SDN 131 Bontobana after the implementation of the board game "Cultural Exploration of Panrita Lopi." This indicates that the game can be used as an effective learning tool in improving students' reading comprehension skills.This research can contribute to knowledge in the field of education and learning. Through this research, new information about the use of the cultural exploration game of Panrita Lopi in improving the reading comprehension skills of Grade V students can be collected and presented, thus helping to expand our understanding of effective learning strategies. This research can also provide a better understanding of the relationship between cultural exploration games and reading comprehension skills. The results of this research can be used to develop better theories and learning models that can be used by educators and researchers in the future.